Multiple Patient Simulation: An Exemplar for Designing an Effective Experience. Issue 1 (January 2019) - Sullivan, Nancy; Goldstein, Nancy; Lucas, Laura; Ockimey, Jessica
Abstract : Supplemental digital content is available in the text.